Anticholinergic Burden and Cognitive Performance in Patients With Schizophrenia: A Systematic Literature Review - Georgiou, Rafaella; Lamnisos, Demetris; Giannakou, Konstantinos (Frontiers in Psychiatry, 2021)
Objective: Cognitive impairment in schizophrenia forms the key cause of the disease’s disability, leading in serious functional and socioeconomic implications. Dopaminergic-cholinergic balance is considered essential to cognitive performance in schizophrenia and patients are often treated with many drugs with anticholinergic properties. This study aims to examine the cognitive impact of anticholinergic burden in patients with schizophrenia. Methods: A systematic literature review was performed on English-language studies published on PubMed, Embase and Web of Science, from inception to June 2021 to identify research studies that examined the effect of anticholinergic load on cognition in clinically stable patients with schizophrenia. No restrictions on study design, age of participants or geographical distribution were applied. Two researchers performed independently the screening and shortlisting of the eligible articles. A narrative synthesis of the main characteristics and findings of studies included was reported. Results: In total, 17 articles of varying methodological design met the inclusion criteria. Three of them found statistically significant improvement in cognition after anticholinergic tapering without adverse effects. Thirteen studies found a statistically significant association between high anticholinergic burden and cognitive impairment (neurocognitive composite scores and individual cognitive domains such as learning and memory, executive function, processing speed), apart from a study, related to the specific characteristics of clozapine. Conclusions: Medication with increased anticholinergic load has been found in most of the studies to negatively affect neurocognitive performance of patients with schizophrenia. However, the clinical and methodological heterogeneity of studies included, limit our interpretation and conclusions.